Monitoring System for Overhead Power Transmission Lines in Smart Grid System Using Internet of Things (University of Khartoum Engineering Journal, 2022)
In the traditional systems, detection of the faults in the electric lines is more difficult. Detection of faults takes time more than repairing time. In most cases faults or problems in power transmission lines occur due to environmental disturbance. Advanced monitoring system of overhead transmission lines assists in saving human lives and helps in maintenance planning. Tension and loosening are examples of problems that result in the absence of high quality monitoring system. The objective of this paper is to do continuous monitoring of the atmospheric conditions and the sag status in the power transmission lines. The design consist of a group of sensors (distance sensor, wind speed sensor, pressure sensor and deviation sensor), which are used to monitor the atmospheric conditions, and send the records to main controller. The controllers transmits these measured values through Wi-Fi to the web page and display them in the channel graph. The recorded resulting data can be shown in a digital form at any time by selecting any point in the graph. The system is built up by using internet of things (IoT)  monitoring technique and global positioning system (GPS) technology to provide the location and guarantee wide range of covering area of the smart grid. The experimental results include the date, time and value and is shown in graphical form to help the manager to analyze the system faults easily. The obtained results were reliable and correct. The results satisfied the goals of the paper and reveal that the use of IoT monitoring system of the transmission lines enhanced the quality of the service.